Learningshift – supporting the future of learning. - Barroca, Ana; Neto, Catarina; Silveira, Ana (Conferência - Investigação e Intervenção em Recursos Humanos, 2019)
The Learningshift project is a European initiative, co-funded by the Erasmus + Programme, and counts with the participation of European higher education institutes (Aalborg University, Tampere University of Applied Sciences, Kaunas University of Technology), training centers (CICCOPN) and enterprises dedicated to the educative field (Advancis, Autens). The project consortium is dedicated to support facilitators and learners following the innovation in education, as it is a first step towards more innovative employees and entrepreneurs. Thus, the Learningshift project will provide the context, the process and the tools for educators to be able to act as facilitators of the 21st (and beyond) learning communities.